Selenium atom on phosphate enhances specificity and sensitivity of DNA polymerization and detection. Issue 28 (1st July 2021) - Luo, Guangcheng; Zhang, Jun; Yang, Mei; He, Hongfei; Huang, Zhen
Abstract : This study reported a unique mechanism of a single selenium-atom modified dNTP to enhance polymerization specificity, enabling us to develop selenium enhanced specific isothermal amplification (SEA) with high specificity and sensitivity. Abstract : DNA polymerization is of high specificity in vivo . However, its specificity is much lower in vitro, which limits advanced applications of DNA polymerization in ultrasensitive nucleic acid detection. Herein, we report a unique mechanism of single selenium-atom modified dNTP (dNTPαSe) to enhance polymerization specificity. We have found that both dNTPαSe (approximately 660 fold) and Se–DNA (approximately 2.8 fold) have lower binding affinity to DNA polymerase than canonical ones, and the Se–DNA duplex has much lower melting-temperature ( T m ) than the corresponding canonical DNA duplex. The reduced affinity and T m can destabilize the substrate-primer–template-enzyme assembly, thereby largely slowing down the mismatch of DNA polymerization and enhancing the amplification specificity and in turn detection sensitivity. Furthermore, the Se-strategy enables us to develop the selenium enhanced specific isothermal amplification (SEA) for nucleic acid detection with high specificity and sensitivity (up to detection of single-digit copies), allowing convenient detection of clinical HPV and COVID-19 viruses in the low-copy number. Clearly, we have discovered the exciting mechanism for enhancing DNA polymerization accuracy, amplification specificity and detection sensitivity by SEA, up to two orders of magnitude higher.